2014
DOI: 10.1080/00103624.2014.983242
|View full text |Cite
|
Sign up to set email alerts
|

Liming in Growing Mango Cultivar Keitt in Production

Abstract: The tropical soil acidity is one of the main limiting factors for crop productivity. This study aimed to evaluate the effects of application of limestone dose to soil fertility, nutritional status of the crop, and productivity and quality of the fruits of mango, cultivar Keitt. The study was carried out at Selvíria, state of Mato Grosso Sul, Brazil, in a Typic Haplustox (pH in CaCl 2 = 4.7), cultivated with mango cultivar Keitt grafted on Coquinho pattern in the production phase (13 years old). Treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(17 reference statements)
0
4
1
2
Order By: Relevance
“…It is observed that the point of maximum accumulated fruit yield of the mango tree, 18,846 kg ha −1 crops (2008/09 and 2009/10) occurred when the soil base saturation index was 51% ( Figure 5). This value is below that suggested by (Quaggio, Van Raij, and Piza Júnior 1997) for the mango crop in the state of São Paulo (V% = 80%) and below that found by (Almeida et al 2008) (V% = 71%) in orchards in production. It should be noted that in the recommendation of (Quaggio, Van Raij, and Piza Júnior 1997), it is not indicated whether the V% refers to mango orchards under implementation or if this recommended value of V% refers to orchards in formation or production.…”
Section: Effect Of Treatments On Plant Nutrition and Yieldcontrasting
confidence: 64%
“…It is observed that the point of maximum accumulated fruit yield of the mango tree, 18,846 kg ha −1 crops (2008/09 and 2009/10) occurred when the soil base saturation index was 51% ( Figure 5). This value is below that suggested by (Quaggio, Van Raij, and Piza Júnior 1997) for the mango crop in the state of São Paulo (V% = 80%) and below that found by (Almeida et al 2008) (V% = 71%) in orchards in production. It should be noted that in the recommendation of (Quaggio, Van Raij, and Piza Júnior 1997), it is not indicated whether the V% refers to mango orchards under implementation or if this recommended value of V% refers to orchards in formation or production.…”
Section: Effect Of Treatments On Plant Nutrition and Yieldcontrasting
confidence: 64%
“…K has an essential role in enzymatic activation, photosynthesis, water use efficiency, formation of starch and protein synthesis (Stino et al, 2011;El-Razek et al, 2013). On the other hand, the excess of K can cause imbalance in the levels of calcium and magnesium (Almeida et al, 2015), which evidences the importance of a good fertilization program. The present study aimed to evaluate soil salinity, number of commercial fruits and yield of mango, cv.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to correct the Ca 2+ level, which is above the optimum values since its highest content is found in mango leaves (Silva et al, 2014), and calcium deficiency can depreciate the quality of the fruit, as low concentration of leaf Ca is associated with the incidence of internal collapse in mango (Almeida et al, 2015). Therefore, higher calcium content in the fruit slows ripening and senescence, by reducing respiration, ethylene evolution and loss of fresh weight, extending post-harvest life and fruit quality of mango (Aular & Natale, 2013;Hojo et al, 2009).…”
Section: Resultsmentioning
confidence: 99%